PROCEDURE FOR THE PROJECTION OF THE DEVELOPMENT OF THE SUGAR INDUSTRY IN A TERRITORY CONSIDERING INTERSECTORAL BALANCE - Wilson González, Fabian Enrique; Galindo Llanes, Pablo A.; Oquendo Ferrer, Hilda de las Mercedes; González Suárez, Erenio (Centro Azúcar Journal, 2023)
Introduction: Consolidating and quantifying information facilitates economic planning for decision making in terms of industrial development at the territorial level in an integrated manner. Objective: To propose a procedure for the projection of the development of the sugar industry in a territory based on the intersectoral balance. Materials and Methods: A procedure is proposed to carry out the intersectoral balance in a territory that facilitates the elaboration of the Leontief matrix. A database “Camagüey Database” is presented in Microsoft Access which, based on the economic survey of each municipality, the units that act in the economy and the demands and deliveries of resources, provides the necessary data for the development of the intersectoral balances. Results and Discussion: The procedure is applied in the territory of Florida where the Central “Agramonte” and the Sorbitol Company are located, belonging to the sugar industry, in function of the territorial industrial development, which facilitates productive linkages and planning between economic sectors. It is defined and quantified the demands and deliveries at 100% compliance of the different sectors that interact for the production of Sorbitol at maximum design capacity. Conclusions: The intersectoral balances allow analyzing the necessary quantities to be produced of each of the products, by-products and derivatives, in correspondence with the demands of other sectors, to guarantee the development of the territory. The results facilitate decision making for a higher development of the municipality in the context of a circular economy.